OpenHELP (Heidelberg laparoscopy phantom): development of an open-source surgical evaluation and training tool - Kenngott, Hannes Götz; Vetter, Josephin; Wagner, Martin; Preukschas, Anas; Wekerle, Anna-Laura; Neher, Peter; Nickel, Felix; Oladokun, Dare; Maier-Hein, Lena; Meinzer, Hans-Peter; Müller, Beat P. (Surgical endoscopy and other interventional techniques, 2015)
Apart from animal testing and clinical trials, surgical research and laparoscopic training mainly rely on phantoms. The aim of this project was to design a phantom with realistic anatomy and haptic characteristics, modular design and easy reproducibility. The phantom was named open-source Heidelberg laparoscopic phantom (OpenHELP) and serves as an open-source platform.
Gesehen am 15.10.2020